Daurichromenic Acid from the Chinese Traditional Medicinal Plant Rhododendron dauricum Inhibits Sphingomyelin Synthase and Aβ Aggregation - Deepak, Hadya Virupaksha; Swamy, Mahadeva M. M.; Murai, Yuta; Suga, Yoshiko; Anetai, Masaki; Yo, Takuro; Kuragano, Masahiro; Uwai, Koji; Tokuraku, Kiyotaka; Monde, Kenji (Molecules, 2020)
Species of the genus Rhododendron have been used in traditional Chinese medicine, with the medicinal herb “Manshanfong” used as an expectorant and for the treatment of acute bronchitis. Daurichromenic acid (DCA), a constituent of Rhododendron dauricum, is a meroterpenoid with antibacterial, anti-HIV, and anti-inflammatory activities. However, the mechanisms underlying these pharmacologic activities are poorly understood. To develop new drugs based on DCA, more information is required regarding its interactions with biomolecules. The present study showed that DCA inhibits the activity of the enzyme sphingomyelin synthase, with an IC50 of 4 µM. The structure–activity relationships between DCA and sphingomyelin synthase were evaluated using derivatives and cyclized hongoquercin A. In addition, DCA was found to inhibit amyloid β aggregation. These results may help in the design of effective drugs based on DCA.